2006
DOI: 10.1016/j.ejcts.2006.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of inosine on reperfusion injury after heart transplantation☆

Abstract: Thus, inosine improves myocardial and endothelial function during early reperfusion after heart transplantation with a persisting beneficial effect against reperfusion induced graft coronary endothelial dysfunction. The effects of inosine are mediated at least partly by modulation of the peroxynitrite-poly(ADP-ribose) polymerase pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 23 publications
1
23
0
1
Order By: Relevance
“…Additionally, nucleosides function as extracellular signalling molecules and, although inosine is only present at low levels in the extracellular space, metabolically stressful conditions such as nflammation dramatically increase the concentration (Hasko et al 2004). Inosine has proved to be a powerful immunomodulatory agent both in vitro (Hasko et al 2000 and in vivo (Hasko et al 2000, Garcia Soriano et al 2001, Mabley et al 2003a,b, Darlington & Gann 2005, Schneider & Klein 2005, Szabo et al 2006. Inosine treatment reduces the production of inflammatory cytokines by murine and human macrophages stimulated by lipopolysaccharide (LPS) in addition to the provided protective effects on both intestinal and vascular function in murine models of endotoxic shock (Hasko et al 2000, Garcia Soriano et al 2001.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, nucleosides function as extracellular signalling molecules and, although inosine is only present at low levels in the extracellular space, metabolically stressful conditions such as nflammation dramatically increase the concentration (Hasko et al 2004). Inosine has proved to be a powerful immunomodulatory agent both in vitro (Hasko et al 2000 and in vivo (Hasko et al 2000, Garcia Soriano et al 2001, Mabley et al 2003a,b, Darlington & Gann 2005, Schneider & Klein 2005, Szabo et al 2006. Inosine treatment reduces the production of inflammatory cytokines by murine and human macrophages stimulated by lipopolysaccharide (LPS) in addition to the provided protective effects on both intestinal and vascular function in murine models of endotoxic shock (Hasko et al 2000, Garcia Soriano et al 2001.…”
Section: Introductionmentioning
confidence: 99%
“…Until recently, inosine was considered an inactive purine metabolite in most biological systems, but several recent studies have shown that it has immuno-modulatory [10], neuroprotective [11], cardioprotective [12] and overall cytoprotective effects. Furthermore, some other studies reported that extracellular inosine has powerful cellular protective effects.…”
Section: Discussionmentioning
confidence: 99%
“…For example, inosine decreases the release of intracellular enzymes from hypoxic lymphocytes [13], improves renal function during ischemia [14] and inhibits inflammatory cytokine production [7]. Administration of inosine has also been shown to improve myocardial function during acute left ventricular failure [15,16] and improve myocardial and endothelial function after heart transplantation [12]. Despite the growing evidence of protective effects of inosine, the use of inosine for prevention of reperfusion injury in the context of cardiopulmonary bypass has not yet been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, inosine can stimulate degranulation of mast cell (Jin et al 1997), inhibit the activation of human neutrophils (Marton et al 2001), reduce the production of proinflammatory cytokines tumor necrosis factor-alpha, interleukin-1, interleukin-12, and counteract the inflammatory response induced by endotoxin (Hasko et al 2000;Liaudet et al 2002). Inosine also may attenuate ischemia-reperfusion injury in the rat heart transplantation model (Szabo et al 2006).…”
Section: Introductionmentioning
confidence: 98%